Barr-i ṣaġīr ke Ahl-i Hadiṯ ḫuddām-i Qurān - Bhat́t́ī, Muḥammad Isḥāq ca. 20./21. Jh. (al-Minār Pabl., 2008)
Biographical sketches of Indian and Pakistani Muslim religious scholars of Ahl-i Hadith sect from 18th to 20th century